ANALYSIS OF CUSTOMERS LOYALTY ON ONLINE SHOPPING PLATFORM DURING PANMDEMIC COVID 19 (CASE STUDY LAZADA ONLINE SHOPPPING PLATFORM) - Jurgen Parera; James D. D. Massie; Emilia M. Gunawan (Universitas Sam Ratulangi, 2023)
The objective of this research is to analyze the customer loyalty on online Shopping Platform Lazada. The sample taken are 11 customer of online shopping platform in University of Sam Ratulangi Manado and from the 4 indicator-Customers tend to use services frequently, Customers are willing to return to use the services, Customers are not interested in switching, Customers will provide positive information to others, Customers will recommend to others that can be collude almost all of the sample are considered as a loyal customer of Lazada customers demonstrate that all those factors, of Customer Loyalty Keywords: customer loyalty